2007
DOI: 10.1556/abiol.58.2007.suppl.8
|View full text |Cite
|
Sign up to set email alerts
|

Definition ofDrosophilahemocyte subsets by cell-type specific antigens

Abstract: We analyzed the heterogeneity of Drosophila hemocytes on the basis of the expression of cell-type specific antigens. The antigens characterize distinct subsets which partially overlap with those defined by morphological criteria. On the basis of the expression or the lack of expression of blood cell antigens the following hemocyte populations have been defined: crystal cells, plasmatocytes, lamellocytes and precursor cells. The expression of the antigens and thus the different cell types are developmentally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
189
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(197 citation statements)
references
References 28 publications
8
189
0
Order By: Relevance
“…Therefore, we investigated whether normal hematopoiesis occurs in senju 1 . Normally, at the late third-instar larval stage, progenitor hemocytes mature into plasmatocytes, crystal cells, and lamellocytes in the lymph gland (13); thus, lymph glands from WT and senju 1 larvae were stained with anti-Nimrod C (a marker of plasmatocytes) (14) and anti-L1 (a marker of lamellocytes) (15) antibodies. In immunologically unchallenged WT larvae, most of the differentiated hemocytes were plasmatocytes, which were located along the outer edge of the lymph gland (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated whether normal hematopoiesis occurs in senju 1 . Normally, at the late third-instar larval stage, progenitor hemocytes mature into plasmatocytes, crystal cells, and lamellocytes in the lymph gland (13); thus, lymph glands from WT and senju 1 larvae were stained with anti-Nimrod C (a marker of plasmatocytes) (14) and anti-L1 (a marker of lamellocytes) (15) antibodies. In immunologically unchallenged WT larvae, most of the differentiated hemocytes were plasmatocytes, which were located along the outer edge of the lymph gland (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have previously identified clusters of sessile hemocytes attached in iterative patterns along the larval cuticle. 2,37,38 These hemocytes are maintained by a niche, 39 express differentiation markers such as hml, and are capable of differentiating into mature hemocyte lineages. A recent report demonstrated that these sessile hemocytes can express the Notch ligand Serrate which is required to signal fellow sessile hemocytes into the crystal cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…1A, arrowheads) showing up as a background fluorescence appearing in all stocks carrying the MiET1 element [16]. The insertion blocks the expression of the Atilla protein encoded by the atilla gene, but does not affect the expression of other, independent lamellocyte-specific markers [10], as L2 and L6 (Fig. 1B,C).…”
Section: Sirmentioning
confidence: 96%
“…Recently Drosophila became a powerful model organism for studying blood cell development and cellular events of innate immunity. The cellular elements of innate immunity, the blood cells or hemocytes in Drosophila, have been characterized by morphological criteria and molecular markers, including transcription factors [6,7] and cell-type specific immunological markers [8][9][10]. In Drosophila, at least three main classes of hemocytes can be discerned.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation